Solid electrolyte, and electrode mixture, solid electrolyte layer, and solid battery using the same
By controlling crystallite sizes and molar ratios in a solid electrolyte with an argyrodite crystal structure, lithium ion conductivity is enhanced, addressing the conductivity challenges in conventional electrolytes with lithium halide presence.
Patent Information
- Application Number
- JP2021553454
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-29
- Filing Date
- 2020-10-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-10-20
AI Technical Summary
Conventional solid electrolytes with an argyrodite crystal structure containing lithium halide face challenges in enhancing lithium ion conductivity, and there is a lack of effective methods to improve conductivity when lithium halide is present.
A solid electrolyte composition with a crystallite size of 60 nm or less for compound B and controlled crystallite sizes for both compound A and B, along with specific molar ratios, is developed to enhance lithium ion conductivity.
The controlled crystallite sizes and molar ratios significantly improve lithium ion conductivity, achieving values of 4.0 mS/cm or more at room temperature, even when lithium halide is present.
Smart Images

Figure 0007601782000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolyte, and an electrode mixture, a solid electrolyte layer, and a solid-state battery using the same. [Background technology]
[0002] In recent years, solid electrolytes have been attracting attention as an alternative to the electrolytes used in many liquid batteries. Solid-state batteries using such solid electrolytes are expected to be put to practical use as batteries that are safer than liquid batteries that use flammable organic solvents, and also have a high energy density.
[0003] As a conventional technique related to solid electrolytes, for example, the technique described in Patent Document 1 is known. This document describes a sulfide solid electrolyte, which is one of the solid electrolytes used in lithium ion batteries. Various crystal structures are known for sulfide solid electrolytes, one of which is the argyrodite-type crystal structure. This document describes that a solid electrolyte containing a compound containing a crystalline phase having an argyrodite-type crystal structure does not contain lithium halide, or if it contains lithium halide, it is desirable that the amount of lithium halide is small. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] US2019 / 305371A1 Summary of the Invention
[0005] It has been believed that it is not easy to increase the lithium ion conductivity of a solid electrolyte containing a compound having a crystal phase with an argyrodite-type crystal structure when the solid electrolyte contains lithium halide as a different phase. In addition, no method for increasing the lithium ion conductivity of a solid electrolyte containing lithium halide has been known. Therefore, an object of the present invention is to increase the lithium ion conductivity of a solid electrolyte containing a compound having a crystal phase with an argyrodite-type crystal structure.
[0006] The present invention relates to a crystalline phase having an argyrodite-type crystal structure, a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less), and a compound B represented by LiX (wherein X is as defined above), The present invention provides a solid electrolyte in which the crystallite size of the compound B is 60 nm or less. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention will be described below based on its preferred embodiments. a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less). Compound A is solid at room temperature (25° C.) and has lithium ion conductivity. The solid electrolyte of the present invention contains, in addition to compound A, compound B represented by LiX (wherein X is defined as above).
[0008] Compound A in the present invention is a crystalline material containing a crystal phase having an argyrodite-type crystal structure. However, compound A may contain a glass component, i.e., an amorphous component. Compound A "containing a crystal phase having an argyrodite-type crystal structure" means that compound A is sufficient to contain at least a crystal phase having an argyrodite-type crystal structure, and may contain a crystal phase (also referred to as a "heterogeneous phase") different from the crystal phase having the argyrodite-type crystal structure. Of course, it is not necessary for compound A to contain the heterogeneous phase. Examples of compounds constituting the heterogeneous phase include Li 3 P.S. 4 Examples include:
[0009] In compound A, the ratio of the crystal phase having an argyrodite crystal structure to all crystal phases constituting compound A may be, for example, 10% by mass or more, 20% by mass or more, or 50% by mass or more. In particular, it is preferable that compound A contains a crystal phase having an argyrodite crystal structure as a main phase. Here, the "main phase" refers to the phase that accounts for the largest proportion of all the crystalline phases constituting the solid electrolyte of the present invention. Therefore, the content of compound A is preferably, for example, 60% by mass or more, more preferably 70% by mass or more, 80% by mass or more, or even more preferably 90% by mass or more, based on the total amount of all the crystalline phases constituting the solid electrolyte of the present invention. On the other hand, the term "heterogeneous phase" refers to a phase that is smaller in proportion than the above-mentioned main phase with respect to the total amount of all crystalline phases constituting the solid electrolyte of the present invention. Therefore, the content of compound B is preferably, for example, 40 mass% or less with respect to all crystalline phases constituting the solid electrolyte of the present invention, and more preferably 30 mass%, 20 mass% or less, or 10 mass% or less. The proportion of the crystalline phase can be determined by calculating the content ratio by, for example, X-ray diffraction measurement.
[0010] The crystal phase having the argyrodite crystal structure has the chemical formula: Ag 8 GeS 6It is particularly preferable that the compound A having a crystal phase having an argyrodite-type crystal structure has a crystal structure belonging to a cubic system from the viewpoint of improving lithium ion conductivity.
[0011] Whether or not the solid electrolyte of the present invention contains compound A including a crystal phase having an argyrodite crystal structure can be confirmed by, for example, XRD measurement. That is, in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation, the crystal phase of the argyrodite crystal structure has characteristic peaks at 2θ=15.34°±1.00°, 17.74°±1.00°, 25.19°±1.00°, 29.62°±1.00°, 30.97°±1.00°, 44.37°±1.00°, 47.22°±1.00°, and 51.70°±1.00°. Furthermore, for example, characteristic peaks are present at 2θ=54.26°±1.00°, 58.35°±1.00°, 60.72°±1.00°, 61.50°±1.00°, 70.46°±1.00°, and 72.61°±1.00°. In this specification, the term "peak" means the apex of a peak. It is preferable that the peaks do not overlap with other peaks and exist independently.
[0012] In the solid electrolyte of the present invention, the crystal phase of the argyrodite-type crystal structure constituting compound A preferably constitutes a major phase with respect to all crystal phases. On the other hand, compound B preferably constitutes a minor phase in the solid electrolyte of the present invention, and is a substance of a different phase from compound A. Therefore, when X-ray diffraction measurement is performed on the solid electrolyte of the present invention, at least a crystal phase of the argyrodite-type crystal structure and a crystal phase derived from compound B are observed.
[0013] In the solid electrolyte of the present invention, it is preferable that the crystallite size of compound B is controlled. In particular, it is preferable that the crystallite size of compound B is controlled to a small value, and thus the lithium ion conductivity of the solid electrolyte of the present invention is improved. The present inventors believe that the reason for this is as follows.
[0014] The solid electrolyte of the present invention contains compound A. When compound A is produced, compound B may inevitably coexist in the product. From the viewpoint of improving the lithium ion conductivity of the solid electrolyte, it is desirable that the amount of compound B is as small as possible, and ideally, compound B does not exist at all. However, in the currently mainstream method of producing compound A, it is not easy to prevent compound B from being present in the product. Therefore, the present inventors have studied various means for improving lithium ion conductivity even when compound B coexists as a different phase in compound A containing a crystal phase having an argyrodite crystal structure. As a result, it has been found that by controlling the crystallite size of compound B, which is a different phase, to a small value, the conduction path of lithium ions in the solid electrolyte is not hindered, and the lithium ion conductivity of the solid electrolyte is improved.
[0015] From the viewpoint of making the above-mentioned advantageous effects more prominent, in the solid electrolyte of the present invention, the crystallite size of compound B is, for example, preferably 60 nm or less, more preferably 57 nm or less, and even more preferably 55 nm or less. In addition, the crystallite size of compound B is, for example, preferably 30 nm or less, more preferably 15 nm or less, and particularly preferably 11 nm or less. The smaller the crystallite size of compound B, the more preferable it is from the viewpoint of improving the lithium ion conductivity of the solid electrolyte. The lower limit of the crystallite size of compound B that can be achieved at the current technical level is about 10 nm, and if the crystallite size of compound B is small to this extent, the lithium ion conductivity of the solid electrolyte will be sufficiently high.
[0016] The crystallite size of the compound B contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. A specific method will be described in detail in the examples described later.
[0017] The solid electrolyte of the present invention exhibits a high lithium ion conductivity of preferably 4.0 mS / cm or more, more preferably 4.5 mS / cm or more, and even more preferably 5.0 mS / cm or more at room temperature (25° C.) by controlling the crystallite size of the compound B contained therein. The lithium ion conductivity of the solid electrolyte can be measured by the method described in the Examples below.
[0018] The compound B contained as a heterogeneous phase in the solid electrolyte of the present invention is represented by LiX as described above. X represents at least one halogen element. Examples of X include fluorine, chlorine, bromine, and iodine. When there is one type of X, the compound B includes LiF, LiCl, LiBr, LiI, and the like. When there are two types of X, the compound B is LiX 1 y X 2 z It is expressed as X 1 and X 2 Each represents a different halogen element. Also, y and z represent numbers greater than 0 that satisfy y+z=1. X 1 and X 2 For example, the combination of Cl and Br (i.e., LiCl y Br z ), a combination of Cl and I, and a combination of Br and I. When X is three types, compound B is LiX 1 y X 2 z X 3 v It is expressed as X 1 , X 2 and X 3 Each of y, z, and v represents a number greater than 0 that satisfies y+z+v=1. 1 and X 2 and X 3An example of the combination is a combination of Cl, Br and I. The solid electrolyte of the present invention may contain only one type of the above-mentioned compound B, or may contain two or more types of compound B. When the solid electrolyte of the present invention contains only one type of compound B, it is preferable that the crystallite size of the compound B satisfies the above-mentioned range. On the other hand, when the solid electrolyte of the present invention contains two or more types of compound B, it is preferable that the crystallite size of at least one type of compound B satisfies the above-mentioned range, and it is more preferable that the crystallite sizes of all compounds B satisfy the above-mentioned range.
[0019] As described above, the compound A contained in the solid electrolyte of the present invention is Li a P.S. b X c Here, "compound A is Li a P.S. b X c "represented by" means that compound A is Li a P.S. b X c In this composition formula, a, which indicates the molar ratio of lithium (Li), is preferably, for example, a number between 3.0 and 6.0, more preferably a number between 3.2 and 5.8, and even more preferably a number between 3.4 and 5.4. Note that a may be less than 5.4. In the composition formula, b, which indicates the molar ratio of sulfur (S), is preferably, for example, a number from 3.5 to 4.8, more preferably from 3.8 to 4.6, and even more preferably from 4.0 to 4.4. Note that b may be less than 4.4. Furthermore, in the composition formula, c is preferably, for example, a number of 0.1 or more and 3.0 or less, more preferably a number of 0.2 or more and 2.5 or less, and even more preferably a number of 0.4 or more and 2.0 or less. Compound A in which a, b, and c are within this range has sufficiently high lithium ion conductivity. In the composition formula, X represents at least one halogen element. When X is one type, compound A is Li a P.S. b Fc , Li a P.S. b Cl c , Li a P.S. b Br c and Li a P.S. b I c When there are two types of X, compound A is Li a P.S. b X 1 y X 2 z It is expressed as X 1 and X 2 Each represents a different halogen element. Also, y and z represent numbers greater than 0 that satisfy c=y+z. X 1 and X 2 Examples of the combination of X include a combination of Cl and Br, a combination of Cl and I, and a combination of Br and I. When X is three types, compound A is Li a P.S. b X 1 y X 2 z X 3 v It is expressed as X 1 , X 2 and X 3 Each represents a halogen element that is different from the others. Also, y, z, and v represent numbers greater than 0 that satisfy c=y+z+v. X 1 and X 2 and X 3 An example of the combination is a combination of Cl, Br and I. The solid electrolyte of the present invention may contain only one type of the above-mentioned compound A, or may contain two or more types of compound A.
[0020] In the present invention, the amount of Li a P.S. b X cCompound A obtained in such a manner may contain elements other than lithium (Li), phosphorus (P), sulfur (S) and halogen (X). For example, it may be possible to replace a part of the lithium (Li) element with another alkali metal element, to replace a part of the phosphorus (P) element with another pnictogen element, or to replace a part of the sulfur (S) element with another chalcogen element.
[0021] In the present invention, in addition to controlling the crystallite size of compound B, it is also preferable to control the crystallite size of compound A. In particular, it is preferable that the crystallite size of compound A is controlled to a small value. As a result, the lithium ion conductivity of the solid electrolyte of the present invention is further improved. From the viewpoint of making this advantageous effect more prominent, in the solid electrolyte of the present invention, the crystallite size of compound A is, for example, preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less. In addition, the crystallite size of compound A is, for example, preferably 71 nm or less, and more preferably 56 nm or less, and particularly preferably 53 nm or less. The smaller the crystallite size of compound A, the more preferable it is from the viewpoint of improving the lithium ion conductivity of the solid electrolyte. The lower limit of the crystallite size of compound A that can be reached at the current technical level is about 40 nm, and if the crystallite size of compound A is small to this extent, the lithium ion conductivity of the solid electrolyte of the present invention will be sufficiently high.
[0022] When the solid electrolyte of the present invention contains only one type of compound A, it is preferable that the crystallite size of the compound A satisfies the above-mentioned range. On the other hand, when the solid electrolyte of the present invention contains two or more types of compound A, it is preferable that the crystallite sizes of all of the compounds A satisfy the above-mentioned range.
[0023] The crystallite size of the compound A contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. A specific method will be described in detail in the examples described later.
[0024] The solid electrolyte of the present invention may contain, for example, impurities in addition to compound A and compound B. From the viewpoint of low influence on performance, the content of the impurities can be, for example, less than 5 mol%, preferably less than 3 mol%, and particularly preferably less than 1 mol%.
[0025] The solid electrolyte of the present invention is composed of a powder as an aggregate of particles. The particle size of the solid electrolyte of the present invention is measured by a volume cumulative particle size distribution measurement method using a laser diffraction scattering type particle size distribution measurement method. 50 The volume cumulative particle diameter D is preferably 2.0 μm or less, more preferably 1.8 μm or less, and particularly preferably 1.5 μm or less. 50 The volume cumulative particle diameter D of the solid electrolyte of the present invention is preferably 0.45 μm or more, more preferably 0.50 μm or more, and particularly preferably 0.55 μm or more. 50 By having the upper limit, the crystallite size of the compound B contained in the solid electrolyte can be made sufficiently small, and the lithium ion conductivity of the solid electrolyte can be sufficiently increased. In addition, when the solid electrolyte of the present invention is used in combination with another solid electrolyte, the solid electrolyte of the present invention is easily inserted into the gaps of the other solid electrolyte. Due to this, the contact points and contact area between the solid electrolytes become large, and the lithium ion conductivity can be effectively improved. On the other hand, the volume cumulative particle size D of the solid electrolyte of the present invention is 50 By ensuring that the lower limit is satisfied, an increase in the surface area of the entire powder of the solid electrolyte can be suppressed, and the occurrence of problems such as an increase in resistance and difficulty in mixing with the active material can be suppressed.
[0026] The above mentioned D 50 In relation to the above, the solid electrolyte of the present invention has a volume cumulative particle size D at 10% by volume of cumulative volume measured by a laser diffraction scattering type particle size distribution measurement method. 10 is preferably 1.0 μm or less, more preferably 0.8 μm or less, and particularly preferably 0.6 μm or less. 10is preferably, for example, 0.0 μm or more, more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. The solid electrolyte of the present invention has a volume cumulative particle size D at 95% by volume cumulative volume measured by a laser diffraction scattering type particle size distribution measurement method. 95 is preferably 8.0 μm or less, more preferably 6.5 μm or less, and particularly preferably 5.0 μm or less. 95 For example, it is preferably 0.50 μm or more, more preferably 0.75 μm or more, and particularly preferably 1.00 μm or more. The volume cumulative particle size D 10 and D. 95 By setting the range as described above, the crystallite size of compound B contained in the solid electrolyte can be made sufficiently small, and an increase in the overall surface area of the powder of the solid electrolyte can be suppressed, thereby making it possible to sufficiently increase the lithium ion conductivity of the solid electrolyte, which is preferable.
[0027] The solid electrolyte of the present invention can be preferably produced by the method described below. As raw materials, a lithium source compound, a phosphorus source compound, a sulfur source compound, and a halogen source compound are used. As the lithium source compound, for example, lithium sulfide (Li 2 As a phosphorus source compound, for example, diphosphorus pentasulfide (P 2 S 5 ) can be used. When the lithium source compound and / or the phosphorus source compound is a sulfide, the sulfide can be used as the sulfur source compound. Compound B (LiX) can be used as the halogen source compound. These raw materials are mixed so that the lithium element, the phosphorus element, the sulfur element, and the halogen element are in a predetermined molar ratio. The mixed raw materials are then fired in an inert atmosphere or in an atmosphere containing hydrogen sulfide gas, thereby producing Li a P.S. b X cA compound containing a crystal phase represented by the formula (I) and having an argyrodite crystal structure is obtained. The atmosphere containing hydrogen sulfide gas may be 100% hydrogen sulfide gas, or may be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. The firing temperature is preferably, for example, 350° C. or higher and 550° C. or lower. The holding time at this temperature is preferably, for example, 0.5 hours or higher and 20 hours or lower.
[0028] The above-mentioned method provides a solid electrolyte containing compound A. A small amount of compound B coexists in this solid electrolyte. The lithium ion conductivity of the solid electrolyte can be increased by controlling the crystallite size of compound B. The inventors have found that it is advantageous to subject the solid electrolyte to a specific pulverization process in order to control the crystallite size of compound B.
[0029] The pulverization process can be performed by a wet or dry method. Various media mills can be used for the pulverization process. As the media mill, a ball mill, a bead mill, a paint shaker, a homogenizer, etc. can be used. As the dispersion media used in the media mill, balls and beads made of various ceramics including alumina and zirconia are used. The diameter of the dispersion media can be, for example, 0.1 mm or more and 50 mm or less.
[0030] When the grinding process is performed by a wet method, it is preferable to use an organic solvent as a dispersion medium, since it can suppress the generation of hydrogen sulfide caused by the reaction between the solid electrolyte and water. Examples of the organic solvent include aromatic organic solvents such as toluene, xylene, benzene, and solvent naphtha, and aliphatic organic solvents such as heptane, decane, normal hexane, cyclohexane, and mineral spirits. These organic solvents can be used alone or in combination of two or more.
[0031] The organic solvent and the solid electrolyte are mixed to form a slurry, and the slurry is subjected to wet pulverization. The concentration of the solid electrolyte contained in the slurry is preferably set to, for example, 5% by mass or more and less than 50% by mass, in order to successfully obtain a solid electrolyte with high lithium ion conductivity. In the wet pulverization using a media mill, the ratio of the dispersion medium to the slurry is preferably 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the slurry, in order to easily obtain a solid electrolyte with high lithium ion conductivity. The dispersion time by the media mill is generally preferably set to 0.5 hours or more and 60 hours or less, in order to easily obtain a solid electrolyte with high lithium ion conductivity.
[0032] When wet grinding is performed, the volume cumulative particle size D of the solid electrolyte after wet grinding is 50 It is preferable to adjust the degree of pulverization so that the volume cumulative particle size D of the solid electrolyte after wet pulverization is preferably 2 μm or less, more preferably 1.8 μm or less, and even more preferably 1.5 μm or less, from the viewpoint of sufficiently reducing the crystallite size of the compound B contained in the solid electrolyte and enhancing the lithium ion conductivity of the solid electrolyte. 50 It is also preferable to adjust the degree of pulverization so that the value is not more than the above-mentioned value from the viewpoint of sufficiently reducing the crystallite size of compound A contained in the solid electrolyte and enhancing the lithium ion conductivity of the solid electrolyte.
[0033] The solid electrolyte of the present invention thus obtained can be used, for example, as a material constituting a solid electrolyte layer or a material contained in an electrode mixture containing an active material. Specifically, it can be used as a positive electrode mixture constituting a positive electrode layer containing a positive electrode active material, or as a negative electrode mixture constituting a negative electrode layer containing a negative electrode active material. Therefore, the solid electrolyte of the present invention can be used in a battery having a solid electrolyte layer, that is, a so-called solid battery. More specifically, it can be used in a lithium solid battery. The lithium solid battery may be a primary battery or a secondary battery, and is preferably used in a lithium secondary battery. The term "solid battery" includes not only a solid battery that does not contain any liquid or gel material as an electrolyte, but also an embodiment that contains, for example, 50% by mass or less, 30% by mass or less, or 10% by mass or less of a liquid or gel material as an electrolyte.
[0034] The solid electrolyte layer in the solid battery can be produced by, for example, dropping a slurry containing the solid electrolyte of the present invention, a binder and a solvent onto a substrate and scraping it off with a doctor blade or the like, contacting the substrate with the slurry and then cutting it with an air knife, forming a coating film by screen printing or the like and then removing the solvent by heating and drying, or the like. Alternatively, the solid electrolyte layer can be produced by press-molding the powder of the solid electrolyte of the present invention and then appropriately processing it. The solid electrolyte layer may contain other solid electrolytes in addition to the solid electrolyte of the present invention. The thickness of the solid electrolyte layer in the present invention is typically preferably 5 μm or more and 300 μm or less, more preferably 10 μm or more and 100 μm or less.
[0035] From the viewpoint of enhancing lithium ion conductivity, the solid electrolyte layer containing the solid electrolyte of the present invention preferably has a porosity of, for example, 50% or less, more preferably 30% or less, and even more preferably 20% or less. The porosity of the solid electrolyte layer can be adjusted, for example, by the pressing pressure when the powdered solid electrolyte of the present invention is made into a compact. The pressing pressure is preferably, for example, 20 MPa or more. The porosity can be calculated from the true density and apparent density of the solid electrolyte layer, which are determined by, for example, a liquid phase method (Archimedes method), using the following relational expression. Porosity (%) = (true density - apparent density) ÷ true density × 100
[0036] It is also possible to use a mixture of the solid electrolyte of the present invention and another solid electrolyte as the solid electrolyte layer. When the solid electrolyte of the present invention is mixed with another solid electrolyte, the solid electrolyte of the present invention can be used in combination with, for example, any of amorphous (glass), glass ceramics, and crystalline materials. When the other solid electrolyte to be mixed with the solid electrolyte of the present invention is a sulfide solid electrolyte, the sulfide solid electrolyte can be specifically Li 2 SP 2 S 5 system, Li 4 P 2 S 6 , Li 7 P 3 S 11 The solid electrolyte to be combined may be a non-sulfide, for example, an oxide-based solid electrolyte.
[0037] The solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and it is preferable that the solid electrolyte layer contains the solid electrolyte of the present invention. Examples of the shape of the solid-state battery include a laminate type, a cylindrical type, and a square type.
[0038] The positive electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a positive electrode active material. As the positive electrode active material, for example, a material used as a positive electrode active material for a lithium secondary battery can be appropriately used. As the positive electrode active material, for example, a spinel-type lithium transition metal compound, a lithium metal oxide having a layered structure, etc. can be mentioned. In addition to the positive electrode active material, the positive electrode mixture may contain other materials such as a conductive assistant.
[0039] The negative electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a negative electrode active material. For example, a negative electrode mixture used as a negative electrode active material of a lithium secondary battery can be appropriately used as the negative electrode active material. For example, the negative electrode active material includes carbon materials such as lithium metal, artificial graphite, natural graphite, and non-graphitizable carbon (hard carbon), lithium titanate, titanium-niobium composite oxide, silicon, silicon compounds, tin, and tin compounds. In addition to the negative electrode active material, the negative electrode mixture may contain other materials such as a conductive assistant. EXAMPLES
[0040] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0041] Example 1 Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Li 2 S powder and P 2 S 5 The powder, LiCl powder, and LiBr powder were weighed. These powders were pulverized and mixed using a ball mill to obtain a mixed powder. The mixed powder was fired to obtain a fired product made of lithium ion conductive sulfide. The firing was carried out using a tubular electric furnace. During the firing, hydrogen sulfide gas with a purity of 100% was circulated through the electric furnace at 1.0 L / min. The firing temperature was set at 450°C and firing was carried out for 4 hours. XRD measurement revealed that the fired product contained a crystal phase with an argyrodite crystal structure and LiCl 0.5 Br 0.5 It was confirmed that the crystal phase was
[0042] The fired material was roughly crushed with a mortar and pestle, then crushed with a hammer crusher, and the crushed material was mixed with a solvent to form a slurry with a concentration of 12% by mass. This slurry was subjected to wet grinding in a bead mill (zirconia beads with a diameter of 0.3 mm). Toluene was used as the solvent for the slurry. Wet grinding was performed for 3 hours using 15 parts by mass of beads for 100 parts by mass of the slurry. After wet grinding, the slurry was separated into solid and liquid, and the solid content was dried. The dried fired material was sieved with a sieve with an opening of 53 μm to obtain the desired solid electrolyte. In addition, other conditions such as grinding time and energy were appropriately selected according to the desired solid electrolyte.
[0043] [Examples 2 and 3] The firing temperature and slurry concentration in Example 1 were changed to the values shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.
[0044] Comparative Example 1 A solid electrolyte was obtained in the same manner as in Example 1, except that the slurry concentration was changed to the value shown in Table 1.
[0045] [Rating 1] The solid electrolytes obtained in the examples and comparative examples were subjected to Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Crystallite size of the crystalline phase and LiCl 0.5 Br 0.5 The crystallite size of the crystalline phase was determined. The volume cumulative particle size D 10 , D 50 , and D 95 The results are shown in Table 1 below.
[0046] [Measurement of crystallite size] A Rigaku SmartLab was used for the measurements. The optical system was focused, with a Johansson monochromator on the incident side and a D / teX Ultra 250 detector. A 5deg Soller slit was used for the incident and receiving parallel slits. A holder not exposed to air was used, the scanning axis was 2θ / θ, the scanning range was 20deg to 140deg, the step width was 0.01deg, and the scanning speed was set so that the maximum peak height was 10,000 counts or more. In addition, SRM660a (compound name: LaB 6 ) was measured under the same conditions and used as the width standard. The analysis was performed using PDXL2 manufactured by Rigaku Corporation. The analysis procedure was as follows. First, identification was performed. The CIF file (Crystallographic Information File) described below was read and the substance was determined. The CIF file was obtained from ICSD (Inorganic Crystal Structure Database). The CIF file with ICSD Collection Code 418490 was used for compound A, and the CIF file with ICSD Collection Code 53818 was used for compound B. Next, intensity resolution was performed with WPPF. For width correction, a width standard data file was selected. This file was used to measure the XRD data of SRM660a and convert it to LaB 6 The file corresponds to a file that was identified by and analyzed in the same manner as the method shown below and saved. The angle and width of the peak were corrected using an external standard sample. The "split-type Pearson VII function" was used as the model function for the peak shape. Next, from the "Basic" tab, "Refinement Parameter Settings" - "Method" selected "Intensity Decomposition". In addition, since the lattice constant changes depending on the combination of X (halogen atoms) in compound B, the initial value of the lattice constant of compound B was adjusted so that the XRD data and the calculated value approximately matched. Next, refinement was performed. In the refinement, various parameters were adjusted until sufficient convergence was achieved. For example, the S value is 1.5 or less as a guideline. The analyzed crystallite size was obtained from "Display" - "Analysis Results".
[0047] [D10 , D 50 , and D 95 Measurement of Using an automatic sample feeder for laser diffraction particle size distribution measurement equipment (Microtrac SDC manufactured by Microtrac-Bell Corporation), the sample (powder) was put into an organic solvent, and after irradiating it with 30W ultrasonic waves for 60 seconds at a flow rate of 50%, the particle size distribution was measured using a laser diffraction particle size distribution measurement equipment (MT3000II manufactured by Microtrac-Bell Corporation), and the D was calculated from the obtained volumetric particle size distribution chart. 10 , D 50 , and D 95 The organic solvent used was toluene.
[0048] [Rating 2] The lithium ion conductivity of the solid electrolytes obtained in the examples and comparative examples was measured by the method described below. The results are shown in Table 1 below. The solid electrolyte was uniaxially pressed in a glove box filled with sufficiently dried Ar gas (dew point -60°C or less). It was further pressed at 200 MPa using a cold isostatic press to produce a pellet with a diameter of 10 mm and a thickness of approximately 4 to 5 mm. Carbon paste was applied to both the top and bottom surfaces of the pellet as electrodes, and then heat treatment was performed at 180°C for 30 minutes to produce a sample for measuring ion conductivity. The lithium ion conductivity of the sample was measured using a Solartron 1255B manufactured by Toyo Corporation. The measurement was performed by an AC impedance method at a temperature of 25°C and a frequency of 0.1 Hz to 1 MHz.
[0049] [Table 1]
[0050] As is clear from the results shown in Table 1, the solid electrolytes obtained in the examples have higher lithium ion conductivity than the solid electrolytes of the comparative examples. [Industrial Applicability]
[0051] According to the present invention, even when a lithium halide is contained in a solid electrolyte that contains a compound including a crystalline phase having an argyrodite-type crystal structure, the lithium ion conductivity can be increased.
Claims
1. It contains a crystal phase having an argyrodite type crystal structure, a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less), LiX (wherein X has the same definition as above), A solid electrolyte, wherein the compound B has a crystallite size of 60 nm or less.
2. 2. The solid electrolyte according to claim 1, having a lithium ion conductivity of 4.0 mS / cm or more at 25° C.
3. The solid electrolyte according to claim 1 or 2, wherein the crystallite size of the compound A is 200 nm or less.
4. The compound B is LiCl y B z 4. The solid electrolyte according to claim 1, represented by the formula: (wherein y and z are numbers that satisfy y+z=1).
5. The solid electrolyte according to claim 1, wherein the volume cumulative particle size D 50 at 50% of the cumulative volume measured by a laser diffraction scattering particle size distribution measurement method is 2.0 μm or less.
6. An electrode mixture comprising the solid electrolyte according to claim 1 and an active material.
7. A solid electrolyte layer comprising the solid electrolyte according to claim 1 .
8. A solid-state battery comprising the solid electrolyte according to any one of claims 1 to 5.
Citation Information
Patent Citations
Sulfide solid electrolyte
JP2018029058A
Sulfide solid electrolyte
US20190305371A1
